Pengaruh Kinerja Perusahaan dan CSR Terhadap Nilai Perusahaan Perbankan Periode 2021-2024 - Jerry Saputra; Siti Khairani (MDP Student Conference, 2026)
This study aims to determine the Effect of Company Performance and CSR on Company Value (Study in the Banking Sector listed on the IDX for the period 2021-2024. In this study the research method used is a quantitative research method. The population of this study is companies in the Banking Sector listed on the Indonesia Stock Exchange (IDX) from 2021-2024. The sample in this study was obtained using a purposive sampling technique totaling 31 companies in the Banking Sector. The data analysis technique used in this study is multiple linear regression. The results of the study show that ROA has a positive and significant effect on PBV, CSRD has no effect on PBV.